2016
DOI: 10.1177/1352458516635874
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue predicts disease worsening in relapsing-remitting multiple sclerosis patients

Abstract: Fatigue is a promising indicator of risk for conversion to confirmed moderate-severe disability in RRMS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…It has also been reported that the contribution of fatigue to depression severity in patients with MS is higher than in idiopathic depressive disorder . Fatigue is not only associated with patient‐reported HRQoL in cross‐sectional and longitudinal analyses, but it is also a predictor of disease activity and progression in patients with CIS and MS .…”
Section: Discussionmentioning
confidence: 96%
“…It has also been reported that the contribution of fatigue to depression severity in patients with MS is higher than in idiopathic depressive disorder . Fatigue is not only associated with patient‐reported HRQoL in cross‐sectional and longitudinal analyses, but it is also a predictor of disease activity and progression in patients with CIS and MS .…”
Section: Discussionmentioning
confidence: 96%
“…We reported on the characteristics of the patients eligible for participating in this study in a previous work . The cohort of participants who contributed to the present study largely overlaps that of our previous work (52 out of 60 subjects) . The criteria to allocate subjects to groups were also similar.…”
Section: Methodsmentioning
confidence: 96%
“…On April 28, 2015, we queried clinical and brain MRI data of a population of over 800 MS patients with quality of life assessment from the CLIMB study database (http://www.climbstudy.org). We reported on the characteristics of the patients eligible for participating in this study in a previous work . The cohort of participants who contributed to the present study largely overlaps that of our previous work (52 out of 60 subjects) .…”
Section: Methodsmentioning
confidence: 99%
“…There is some evidence that a shorter time to CDMS diagnosis might correlate with a more severe disease course with more disability. 27 Cavallari et al 28 found that fatigue in patients with MS was predictive for disease worsening. Therefore, we tested whether fatigue present even earlier in the disease also predicts future disability.…”
Section: Discussionmentioning
confidence: 99%